Longitudinal double-spin asymmetry for inclusive jet and dijet production in polarized proton collisions at √s=510 GeV - Abdallah, Mohamed Samy; Deppner, Ingo Martin; Herrmann, Norbert; Söhngen, Yannick; Weidenkaff, Philipp (Physical review, 2022)
We report measurements of the longitudinal double-spin asymmetry, ALL, for inclusive jet and dijet production in polarized proton-proton collisions at midrapidity and center-of-mass energy √s=510 GeV, using the high luminosity data sample collected by the STAR experiment in 2013. These measurements complement and improve the precision of previous STAR measurements at the same center-of-mass energy that probe the polarized gluon distribution function at partonic momentum fraction 0.015≲x≲0.25. The dijet asymmetries are separated into four jet-pair topologies, which provide further constraints on the x dependence of the polarized gluon distribution function. These measurements are in agreement with previous STAR measurements and with predictions from current next-to-leading-order global analyses. They provide more precise data at low dijet invariant mass that will better constrain the shape of the polarized gluon distribution function of the proton.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
STAR Collaboration: M.S. Abdallah, I.M. Deppner, N. Herrmann, Y. Söhngen, P.C. Weidenkaff [und viele weitere Personen]
Gesehen am 01.09.2022